Geology and petrogenetic considerations of the Loma Marcelo skarn, Neoproterozoic basement of the Ventania System, Argentina - Ballivián Justiniano, Carlos Alberto (2017)
The Late Precambrian–Early Palaeozoic crystalline basement of the Ventania System is mainly composed of Neoproterozoic S-type granites, Early Cambrian alkaline granites, and Middle Cambrian peralkaline rhyolites. The Neoproterozoic granites (ca. 607–581 Ma) crop out in the Cerro Pan de Azúcar-Cerro del Corral area and host the Loma Marcelo Ca/Mg skarn, composed of calc-silicate- and chondrodite-bearing assemblages. Petrographical, geochemical, and geochronological data indicate that the skarn was formed from carbonate xenoliths of sedimentary nature incorporated during the intrusion of the Neoproterozoic granites and that it is the result of three successive metamorphic events. The first one is related to the incorporation of carbonate xenoliths by the intrusion and the associated contact metamorphism. The second event is linked to the crystallization of the Early Cambrian granites and related post-magmatic processes. They are responsible for fluorine influx into the Neoproterozoic basement, which resulted in the formation of high-F minerals in the Loma Marcelo skarn (e.g. vesuvianite, chondrodite). The Sm-Nd garnet-whole rock isochron age of 526.8 ± 12.0 Ma in the skarn confirms its relationship with the Early Cambrian magmatism. The last event corresponds to a regional metamorphism assigned to the Late Devonian–Early Carboniferous on the basis of a LA-ICP-MS U-Pb age of 353.4 ± 6.7 Ma determined on zircons of the skarn as well as a Rb-Sr quartz-sericite isochron age of 364.4 ± 3.6 Ma obtained from a quartz vein that post-tectonically cuts the already mylonitized granites. The different chemical compositions of the carbonate protoliths determined the formation of two types of skarns of calcic and magnesian compositions. A single date of the calcic skarn defined a LA-ICP-MS U-Pb upper intercept age of 648 ± 21 Ma, providing the maximum sedimentation age for the calcic protolith of the Loma Marcelo skarn. The minimum sedimentation age is provided by the crystallization age of the S-type granite surrounding the skarn (ca. 607 Ma). The Loma Marcelo skarn reveals the occurrence of underground Neoproterozoic carbonate (meta-?) sedimentary rocks as part of the basement of the Ventania System. These rocks could correlate with the carbonate sequences of the neighbouring Claromecó Basin and Tandilia System.